Analisis Sharih Akad Mudrobah dan Bay pada Sertifikat Investasi Mudharabah Antar Bank (SIMA) - Arivatu Ni'mati Rahmatika; Dunyati Ilmiah (Koordinatorat Perguruan Tinggi Keagamaan Islam Swasta Wilayah IV Surabaya, 2017)
Sertifikat Investasi Mudorobah Antarbank is called SIMA, is the one of instrument Islamic InterBank Money Market. And the others is Sertifikat Investasi komoditi antarbank is called SiKA.. The aim this research for giving a knowledge about the akad and application of SIMA, and also to know the compliant between akad and application. The method of this research is kualitatif method. the data is used by researcher is kualitatif data. The source of data is primer and secunder data. In this research, is using content analysis with comparative-descriptive. The result of this research is the ‘M’ in SIMA must be replaced to be Musharokah, the Bay’ in SIMA is not relevant with the akad, because in application the object of bay’ akad is sertificate, it is same as money trading.